The prognostic factors of diabetic retinopathy severity among type 2 diabetes mellitus in a tertiary teaching hospital - Aniza, Abd Aziz; Wan Mohd Razin, Wan Hassan; Syaratul Emma, Hashim (Malaysian Public Health Physicians Association, 2016)
Diabetic retinopathy (DR) may result in progressive visual impairment and blindness which affects the diabetic patients‟ morbidity and quality of life significantly. The objective of this study was to determine the proportions and prognostic factors of DR severity among Type 2 diabetes mellitus patients. A cross sectional study was conducted at the Ophthalmology Clinic in a tertiary hospital using the medical record database from 2005 to 2011. A total of 216DR patients were randomly selected. The study outcome was DR severity which was classified into four grading based on the International Clinical Diabetic Retinopathy Scale. Descriptive statistics and Ordinal Logistic Regression were applied using Stata SE/11. The mean (SD) age of DR in this study was 56.06 (9.98) years old with almost equal sex ratio. Proportion of mild non proliferative diabetic retinopathy (NPDR) was 48.6% (95% CI: 40.0, 60.0), moderate NPDR was 28.2% (95%CI: 22.0, 40.0), severe NPDR was 6.9% (95% CI: 4.0, 11.0) and proliferative diabetic retinopathy (PDR) was 16.2% (95%CI: 10.0, 22.0). Diabetic patients that suffered from diabetes mellitus for more than 10 years, having nephropathy, every increased of HbA1c by 1% and higher total cholesterol were at increased risk of worsening DR.Diabetic retinopathy (DR) may result in progressive visual impairment and blindness which affects the diabetic patients‟ morbidity and quality of life significantly. The objective of this study was to determine the proportions and prognostic factors of DR severity among Type 2 diabetes mellitus patients. A cross sectional study was conducted at the Ophthalmology Clinic in a tertiary hospital using the medical record database from 2005 to 2011. A total of 216DR patients were randomly selected. The study outcome was DR severity which was classified into four grading based on the International Clinical Diabetic Retinopathy Scale. Descriptive statistics and Ordinal Logistic Regression were applied using Stata SE/11. The mean (SD) age of DR in this study was 56.06 (9.98) years old with almost equal sex ratio. Proportion of mild non proliferative diabetic retinopathy (NPDR) was 48.6% (95% CI: 40.0, 60.0), moderate NPDR was 28.2% (95%CI: 22.0, 40.0), severe NPDR was 6.9% (95% CI: 4.0, 11.0) and proliferative diabetic retinopathy (PDR) was 16.2% (95%CI: 10.0, 22.0). Diabetic patients that suffered from diabetes mellitus for more than 10 years, having nephropathy, every increased of HbA1c by 1% and higher total cholesterol were at increased risk of worsening DR.